Complex RNA chain elongation kinetics by wheat germ RNA polymerase II. - Job, D (1984)
Kinetics of RNA chain elongation catalyzed by wheat germ RNA polymerase II have been studied using various synthetic DNA templates in the presence of excess dinucleotide monophosphate primers. With single- or double-stranded homopolymer templates, the double reciprocal plots 1/(velocity) as a function of 1/(nucleotide substrate) exhibit positive, negative or no curvature. With poly(dAT) as template, the mechanism of nucleoside monophosphate incorporation into RNA is not the ping-pong kinetic mechanism which was derived for E. coli RNA polymerase (6). Noncomplementary nucleoside triphosphates inhibit RNA transcription allosterically. Cordycepin triphosphate behaves as ATP, and not only inhibits AMP incorporation but also that of UMP and GMP on appropriate templates. The reason for this complex kinetic behavior is not yet understood. Possibilities are raised that there are several nucleoside triphosphate binding sites on wheat germ RNA polymerase II, that additional nucleoside triphosphate dependent enzymatic activities are required for reaction to occur or that the Km value for incorporation of a given nucleoside monophosphate into RNA is dependent on the length of the RNA chain and/or the nucleotide sequence surrounding the complementary base on the DNA template.